Introduction to Sumba’s traditional typical woven fabric motifs based on augmented reality technology - Fairuz Iqbal Maulana; Bening Insaniyah Al-Abdillah; Ruth Rade Awang Pandango; Andini Putri Maharani Djafar; Frihandhika Permana (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Sumba woven cloth is one of the points of pride in East Sumba and West Sumba. The process of making Sumba woven cloth is not easy, making the patterned cloth is really valuable. These various motifs have their own stories behind them. Sumba woven fabric is one of the cultural heritages that must be preserved. One way to preserve this cultural heritage is implementing technological developments, such as augmented reality (AR) technology on smartphones. The combination of culture and technology can play a role in preserving Indonesia's cultural diversity. In applying this technology, we use the analysis, design, development, implementation, and evaluation (ADDIE) method starting from the stages of analysis, design, development, implementation, and evaluation. In an implementation, there will be a woven fabric catalog book that becomes a marker to bring up a 3D model of Sumba woven fabric that has been knitted in the form of clothes. The results revealed that the shortest distance between the marker and the camera at which 3D objects may be displayed is 20 cm, and the marker's reading angle is just approximately 0°-45°. The average duration observed is 0.056 seconds, and the average speed obtained is 8.92 meters per second.